Chemical and biological treatments of seeds of Aniba rosaeodora for the control of Heilipus odoratus (Coleoptera, Curculionidae, Molytinae) in greenhouses, Amazonas, Brazil - Arispe Torrez, Adrian Arturo; Ramos Chevreuil, Larissa; Alves de Sousa, Kally; de Tarso Barbosa Sampaio, Paulo; Souza Bruno, Flávio; Sales-Campos, Ceci (BOSQUE, 2018)
Aniba rosaeodora is a species of high international commercial value due to the essential oil in the wood, branches and leaves. Studies indicate problems in the annual production of fruits and seeds, due to intense insect attack, which is a limiting factor in the production of seedlings. The present study evaluates the efficiency of the insecticide (Karate Zeon 50 CS) and the extract of an entomopathogenic fungus Beauveria bassiana on the control of the larva of Heilipus odoratus in seeds and their influence on the initial development of the seedlings. In the first experiment, seeds were collected from the forest floor and tree canopy, later they were immersed in a liquid solution of 5 mL L-1 Karate Zeon insecticide for 24, 48 and 72 hours. In the second experiment, the seed were immersed in a concentration of 106 conidia mL-1 of B. bassiana and incubated in an orbital mixer for 3 hours at 180 rpm at 30 °C. To continue, the seeds were collected to be germinated in a substrate of vermiculite (28 ± 3 °C) for 60 days; afterward, they were placed in 1 kg plastic bags and grown in a greenhouse with (50 %) shade and a daily mist for 270 days. The parameters evaluated were: percentage of germination (G%), index of germination velocity (IGV), average germination time (AGT), growth, biomass (root, stem and leaves), chloroplast pigments content and leaf gas exchange. Results indicate that the treatments of seeds diminished the damage caused by the larva of H. odoratus increasing the index of germination without affecting the initial development.